Best paper award in the 20th International Workshop on Semantic and Social Media Adaptation & Personalization (SMAP 2025) - Tsapatsoulis, Nicolas (My University, 2026)
M. C. Voutsa, N. Tsapatsoulis, C. Djouvas and C. Andreou, "Bias in the Machine: Cross-Model Evaluation of ChatGPT-4 and Qwen in Hotel Booking Review Annotation," 2025 20th International Workshop on Semantic and Social Media Adaptation and Personalization (SMAP), Mystras, Greece, 2025, pp. 81-85, doi: 10.1109/SMAP66932.2025.00023.
Keywords: Sciences